(untitled) (International Journal of Nursing Education, 2023)
Background: Cervical cancer is a common cancer in the world, Pap smear and human papilloma virus test are used for early detection and follow up of cervical cellular changes and cervical cancer, but here in Sudan they are still poorly used. Diabetes and cancer share some risk factors and they have both been found to happen in the same patients. The aim of this study is to evaluate abnormal pap smears from diabetics and non-diabetics.Methods: this is a case-control hospital base study, (109) cases and (109) controls, the patients who requested pap smear during study period and who matched the characteristics of the study. Controls are diabetes-free, but they have another complains because of which the pap smear is requested like genital infection complaints or gynecological complaints, cases have diabetes plus the infection or gynecological complaints because of which the pap smear is requested.Results:(74.3%) of the cases showed abnormal results (positive), (47.6%) of them Atypical Squamous Cells of Undetermined Significance and Atypical Glandular Cells of Undetermined Significance, (26.7%) of them inflammation and infection. (22.9%) of the controls showed positive results (4.6%) of them Atypical Squamous Cells of Undetermined Significance and Atypical Glandular cells of Undetermined Significance, (18.3%) of them signs of inflammation and infection signs. (25.7%) of the cases have had negative pap results for intraepithelial lesion, malignancy, or infections while (77.1%) of control.Conclusions: there is association between diabetes mellitus and abnormal finding of pap smear test and controlling of diabetes mellitus is important issue affecting pap smear findings. also, diabetes increases liability of diabetic women to get infections and cervical cellular changes.